TINJAUAN YURIDIS TERHADAP TINDAKAN HAKIM DALAM MENILAI KEKUATAN ALAT BUKTI KETERANGAN SAKSI YANG BERBEDA ANTARA DIDEPAN PENYIDIK DENGAN DI PERSIDANGAN - Hilman Nurrachman (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACTThe community is appropriate and useful by determining what is required or permissible and vice versa. Acts that are in accordance with the law are not a problem and need not be questioned, the problem is the act that is against the law so that all forms of crime can be resolved as fairly as possible, and with the existence of the law is also expected to avoid the occurrence of violations that can be done by the public or law enforcement itself.This study uses normative legal research, which is a legal research method carried out by examining mere lirature or secondary data. The research procedure used is the research of collecting legal material that will be used in this research is the study of literature that is collecting data by reading legislation, official documents, and literature that are closely related to the issues discussed.The results of the study explained that the judge's actions in assessing the strength of the evidence of witness testimony were different between in front of the investigator and at the trial namely by the judge asking the reason for the witness giving different information, the judge then asked for witnesses to be verbally presented.The judge can remind the witness that if the statement submitted is not true then the witness can be convicted for providing false testimony/oath and criteria for evidence of witness testimony that is judged to be valid by the judge. evidence, that is, witness statements deemed valid are witness statements given under oath Keywords: Evidence and Witnesses